2020
DOI: 10.1016/j.anr.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The Indonesian Version of the Exercise Self-Efficacy Scale: Cross-cultural Adaptation and Psychometric Testing

Abstract: The study aimed to translate the Exercise Self-Efficacy Scale (ESES) into Indonesian and test the cultural equivalence, reliability, and validity of the new version for university students. Methods: The cross-sectional study recruited 379 Indonesian university students using convenience sampling. Phase 1, a culturally appropriate version of the ESES was developed in the Indonesian language. Phase 2, the psychometric properties were determined through exploratory factor analysis, bootstrap factor analysis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The questionnaire instrument that measures self-efficacy in T2DM patients used the Exercise Self-Efficacy Scale (ESES) which is a valid, reliable, and stable tool to assess self-efficacy in T2DM in Indonesia. 14 This instrument has a content validity index (CVI) score of 0.80–1.00. The Cronbach alpha of the Indonesian version of DQoL-BCI is A Cronbach is 0.78, 0.80, and 92 which means it shows adequate results.…”
Section: Data Analysis and Instruments Of Validity And Reliabilitymentioning
confidence: 99%
“…The questionnaire instrument that measures self-efficacy in T2DM patients used the Exercise Self-Efficacy Scale (ESES) which is a valid, reliable, and stable tool to assess self-efficacy in T2DM in Indonesia. 14 This instrument has a content validity index (CVI) score of 0.80–1.00. The Cronbach alpha of the Indonesian version of DQoL-BCI is A Cronbach is 0.78, 0.80, and 92 which means it shows adequate results.…”
Section: Data Analysis and Instruments Of Validity And Reliabilitymentioning
confidence: 99%
“…Previous studies over the last two decades reported that one of three college students tend to become more physically inactive throughout their college years (Huang et al, 2003;Kolodinsky et al, 2007). Several reasons that might explain the findings are due to rapid technology development (Ráthonyi et al, 2021), lack of motivation (Eichorn et al, 2018), and academic pressures (Hakim et al, 2020). Students often do not have time to do physical activities or any kind of sport because they are busy with lectures and assignments (Supriyanto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Third, the Exercise Self-Efficacy Scale (ESES) describes a situation where a person has difficulty following routine activities. This questionnaire is already in the Indonesian edition, which has gone through the process of adaptation and psychometric test with good results (Hakim, A. R., Wang, S. T., Widiantoro, F. X., Hannan, M., Wang, C. J., & Fetzer, 2020).…”
Section: Introductionmentioning
confidence: 99%